2022
DOI: 10.1186/s12960-022-00729-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the first two Frontline cohorts of the field epidemiology training program in Guinea, West Africa

Abstract: Background The 2014–2016 Ebola virus disease outbreak in West Africa revealed weaknesses in the health systems of the three most heavily affected countries, including a shortage of public health professionals at the local level trained in surveillance and outbreak investigation. In response, the Frontline Field Epidemiology Training Program (FETP) was created by CDC in 2015 as a 3-month, accelerated training program in field epidemiology that specifically targets the district level. In Guinea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Table 1 presents the characteristics of the studies along with a summary of their findings. The evaluations covered the three different program modalities in various countries or regions, including Yemen ( 12 ), Ethiopia ( 13 , 14 ), Guinea ( 15 ), Tanzania ( 16 ), United Kingdom ( 17 ), South Africa ( 18 ), Kenya ( 19 ), Ghana ( 20 ), India ( 9 ). Two studies evaluated the FETPs in selected countries in the EMR ( 7 , 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the characteristics of the studies along with a summary of their findings. The evaluations covered the three different program modalities in various countries or regions, including Yemen ( 12 ), Ethiopia ( 13 , 14 ), Guinea ( 15 ), Tanzania ( 16 ), United Kingdom ( 17 ), South Africa ( 18 ), Kenya ( 19 ), Ghana ( 20 ), India ( 9 ). Two studies evaluated the FETPs in selected countries in the EMR ( 7 , 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The integration of IDSR and DHIS 2 into Field Epidemiology Training Program curriculum and mentoring activities helped to reinforce implementation of the tools. A 2018 evaluation of Guinea's Field Epidemiology Training Program reported that graduates of the training program for frontline workers were able to identify the necessary procedures and tools to conduct disease surveillance tasks at their level, including data collection, reporting, analysis and evidence-based decision-making ( 23 ). Although this evaluation was conducted before the completion of IDSR and DHIS 2 scale-up, it suggests that the synergy between these three activities can be leveraged to increase uptake and reinforce effective use of IDSR tools, including DHIS 2.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of FETP-Frontline in other countries also documented the effectiveness of the program. Studies conducted in Guinea [ 36 ], Liberia [ 37 ], Zambia [ 22 ] and Kenya [ 38 ] documented that the trained officers had improved capacity. Effectiveness of FETP-Frontline has also been reported with regards to improved surveillance data, quality surveillance reports, case investigations, outbreak investigations, and surveillance system improvements.…”
Section: Discussionmentioning
confidence: 99%